2022
DOI: 10.1021/acs.jmedchem.2c01361
|View full text |Cite
|
Sign up to set email alerts
|

Targeting Gatekeeper Mutations for Kinase Drug Discovery

Abstract: Clinically acquired resistance is a major challenge in cancer therapies with small-molecule kinase inhibitors (SMKIs). Gatekeeper mutations in the ATP-binding pocket of kinases are the most common mutations leading to acquired resistance. To date, seven new-generation kinase inhibitors targeting gatekeeper mutations have been approved by the FDA; however, the clinical need is still unmet. Here, we systematically summarize the types of gatekeeper mutations across the kinase family, the structural basis for acqu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
20
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 28 publications
(25 citation statements)
references
References 121 publications
(215 reference statements)
0
20
0
Order By: Relevance
“…Therefore, the development of antitumor drugs targeting protein kinases has admiring all-encompassing attention. Up to now, a total of more than 70 kinase inhibitors have been launched for various diseases such as cancer, neurological disorders, inflammation, and metabolism, rendering kinase to become a major class of drug targets . Here, three launched and one preclinical kinase molecule that do not belong to USPTO-50K were used to demonstrate the utility and good generalization of our approach in drug discovery.…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, the development of antitumor drugs targeting protein kinases has admiring all-encompassing attention. Up to now, a total of more than 70 kinase inhibitors have been launched for various diseases such as cancer, neurological disorders, inflammation, and metabolism, rendering kinase to become a major class of drug targets . Here, three launched and one preclinical kinase molecule that do not belong to USPTO-50K were used to demonstrate the utility and good generalization of our approach in drug discovery.…”
Section: Resultsmentioning
confidence: 99%
“…In addition, it would be an even more difficult task to experimentally validate all 1186 potentially active peptides due to the time-consuming and costly nature of chemical synthesis and bioactivity assays experiments. However, the studies of traditional discovery of biologically active molecules have sufficiently demonstrated that mutating a small portion of the fixed backbone can generates new active molecules. , Therefore, it is often crucial to consider sequence similarity in the discovery of target active peptides. Here, we only selected similar sequences to the unique potential inhibitor 17C-L20 obtained during the data set construction process for affinity determination, as peptides with high sequence similarity were more likely to had similar properties and small variations at the amino acid level could result in significant changes in activity .…”
Section: Resultsmentioning
confidence: 99%
“…Gatekeeper mutations represent the most common acquired "on-target" mutations responsible for inducing resistance. 128 Specifically, RET V804M/L gatekeeper mutations serve as a major resistance mechanism for first-generation MKIs. These mutations can manifest as germline mutations in sMTC and in approximately 2% of MEN2 cases.…”
Section: Limitations Of Approved Mkis While These Mkis Can Produce Be...mentioning
confidence: 99%